PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN MARKETING PADA PT.UNITED TRACTOR ( UNTR ) TBK, CAKUNG JAKARTA - Lita Kurnia Sari; Rivera Pantro Sukma (Human Capital Development, 2016)
Purpose- This Research to analyse influence of compensation, and achievement work to employee capacity performance on PT. United Tractor (UNTR) Cakung Jakarta Design/methology/approach- This research population in the marketing division of 100 people by using sample. Data analyzer used in examination of hypothesis is double linear regression analysis. Findings- Result employees where compensation significant effect on the performance of employees and the work echievement influence on employee performance. It is also found that about 50.9 % were influenced by other variables. Research limitations- The limitation of this research lies on its scope of object, and the limited variables involved. It is then suggested for the next research that other variable such as motivation, and other exogen variable can be deployed too. Practical implications- The manager of human resource shall maintain and develop the potential of employees by providing a combination of training and motivation in human resources development. The Originality- This is done exclusively for the P.T. United Tractor as a single company that may applicable therein